THE IMPORTANCE OF TAX AMNESTY POLICY IN EFFORTS TO OVERCOME TAX EVASION IN INDONESIA - Imas Sholihah (Jurnal Dinamika Hukum, 2016)
Fundamental problems of taxation in Indonesia is a low tax ratio and management of the tax systemhas not been well ordered, especially the handling of the tax evaders. Tax amnesty policy is presentas one of the solutions of the problems of taxation and is part of the tax reform. There are pros andcons to this policy as it pertains to the settings in the Tax Forgiveness Act is considered less sense offairness and legal certainty and are vulnerable to abuse of authority. This policy became importantalthough it is less sense of fairness if the review facilities subject to tax amnesty even though thestate would get the revenue the state in large numbers in a short period of short-term benefits, butif managed by the management and human resources professionals, socialization, and optimizedcontrol, a long-term positive impact to minimize state income tax evasion.Keywords: tax amnesty, policy, tax evation (avoidance)